Formulasi dan Evaluasi Mutu Fisik Lip balm dari Ekstrak Kulit Buah Hylocereus lemairei dengan Variasi Konsentrasi Cera Alba - Suena, Ni Made Dharma Shantini; Intansari, Ni Putu Ocha Indira; Suradnyana, I Gede Made; Mendra, Ni Nyoman Yudianti; Antari, Ni Putu Udayana (Usadha, 2022)
Red dragon fruit skin (Hylocereus lemairei) contains flavonoid compounds (polyphenols), and vitamins C and E which play the main role as antioxidants, so they are good for moisturizing, nourishing, and maintaining skin health. Lip balm is a cosmetic preparation with main components such as waxes, fats, and oils from natural or synthesized extracts to prevent dryness by increasing lip moisture. The stability of preparation is very important in maintaining the physical quality of the preparation until it reaches the consumer. This study aims to determine the concentration of Cera alba as a stiffening agent needed to produce lip balm preparations of red dragon fruit skin extract (Hylocereus lemairei) with good physical quality. The response observed was the physical quality of the lip balm preparation which included organoleptic, homogeneity, pH, adhesion, and mechanical strength of the lip balm. Data analysis was carried out descriptively. This research begins with the extraction process of red dragon fruit skin using an ultrasonic wave-assisted maceration method using 96% ethanol and 1% HCl. In this study, a lip balm formulation was made from red dragon fruit peel extract with various concentrations of Cera alba 5% (F1), 10% (F2), and 15% (F3) as a stiffening agent. The resulting preparations were stored for 28 days, and their physical quality was observed. The results showed that lip balm preparations F3 produced good physical quality of lip balm preparations during storage. Dragon fruit peel extract can be properly formulated using Cera alba at a concentration of 15% to become a lip balm preparation that has high-quality physical characteristics and has the potential to be developed into a cosmetic preparation that is able to maintain skin moisture, especially the lips.